La Divina Commedia di Dante: Inferno - Dante Alighieri, 1265-1321 (Salt Lake City, UT : Project Gutenberg, 1997)
"La Divina Commedia di Dante: Inferno" by Dante Alighieri is a narrative poem written in the 14th century. It follows a fictionalized Dante through Hell, guided by the Roman poet Virgil. Lost in a dark wood at age thirty-five, Dante must journey through nine concentric circles of torment deep within the Earth. Each circle punishes sinners in ways that mirror their earthly crimes. This allegorical descent represents the soul's recognition and rejection of sin on its path toward God. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Inferno_(Dante) https://it.wikipedia.org/wiki/Inferno_(Divina_Commedia)
Release date is 1997-08-01
an anonymous Project Gutenberg volunteer
Keywords: Italian poetry -- To 1400; Hell -- Poetry; Epic poetry, Italian